Pengaruh Punishment dan Budaya Organisasi terhadap Disiplin Kerja Karyawan PT. Charman Putra Interbuana - Yolincia Yolana; Syawaluddin Syawaluddin; Mila Asmawiani Okta; Thomas Sumarson Goh (Universitas Batanghari Jambi, 2022)
Work discipline is defined as an attitude, behavior, and actions that are in accordance with the regulations of the organization in written or unwritten form. One of the factors that influence work discipline is punishment. Punishment or punishment is: to improve discipline and educate employees to comply with all company regulations. Other factors that influence employee work discipline are: organizational culture. Organizational culture can influence the behavior of members of the company to be disciplined. The purpose of this study was to determine the effect of punishment and organizational culture on the work discipline of employees of PT. Charman Putra Interbuana. The research method used is a survey approach analysis method, the type of research is quantitative descriptive, the research method is carried out by questionnaires, interviews, and documentation studies. The analytical method used is multiple linear regression. The population is employees of PT. Charman Putra Interbuana. The sample in the study to be tested is 35 people. The data analysis technique used is the reliability validity test, the classical assumption test, the coefficient of determination (R2) test, multiple regression analysis, and hypothesis testing. The results of this study indicate that punishment and organizational culture simultaneously affect the work discipline of employees of PT Charman Putra Interbuana Medan. The punishment variable partially has a significant effect on work discipline, while organizational culture partially has no effect on work discipline. Punishment and organizational culture explain its influence on the work discipline of employees of PT. Charman Putra Interbuana with a coefficient of determination of 0.293 which means 29.3% and the remaining 70.7% is varied by other factors not examined such as motivation, compensation and others